2017
DOI: 10.3389/fncel.2017.00183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proestrus on Gene Expression in the Medial Preoptic Area of Mice

Abstract: The antero-ventral periventricular zone (AVPV) and medial preoptic area (MPOA) have been recognized as gonadal hormone receptive regions of the rodent brain that—via wiring to gonadotropin-releasing hormone (GnRH) neurons—contribute to orchestration of the preovulatory GnRH surge. We hypothesized that neural genes regulating the induction of GnRH surge show altered expression in proestrus. Therefore, we compared the expression of 48 genes obtained from intact proestrous and metestrous mice, respectively, by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…In addition to its key role in the expression of parental and sexual behavior [38][39][40] , the mPOA is involved in neuroendocrine functions as the secretion of gonadotropin-releasing hormone, among other endocrine mediators 41 . As pointed out by Horii-Hayashi et al, in cycling females the mPOA would require high levels of neural plasticity, both structurally and synaptically, to adequately respond to the hormonal levels in the circulation, a fact that might explain the absence of PNNs 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its key role in the expression of parental and sexual behavior [38][39][40] , the mPOA is involved in neuroendocrine functions as the secretion of gonadotropin-releasing hormone, among other endocrine mediators 41 . As pointed out by Horii-Hayashi et al, in cycling females the mPOA would require high levels of neural plasticity, both structurally and synaptically, to adequately respond to the hormonal levels in the circulation, a fact that might explain the absence of PNNs 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have demonstrated that kisspeptin neuron populations of the AVPV region and the kisspeptin/neurokininB/dynorphin (KNDy) neurons of the arcuate nucleus (ARC) mediate the positive and negative feedback actions of E2 toward the GnRH system ( Smith et al, 2005 ; Kalló et al, 2012 ; Clarkson et al, 2017 ; Lunenfeld and Buhler, 2017 ; Vastagh and Liposits, 2017 ). Human mutations and knock out animals clearly showed the importance of these indirect pathways in the feedback regulation of GnRH neurons ( Mayer and Boehm, 2011 ; Brioude et al, 2013 ; Ratnasabapathy and Dhillo, 2013 ; Demirbilek et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last century, lesion experiments revealed that neural activity located in the medial preoptic area (MPOA) region of the hypothalamus is crucial to initiate parental care [6,7]. This area of the brain is composed of a variety of neuron types each expressing different neurotransmitters, neuropeptides, and receptors [8], yet only a subset is likely to promote parenting because the MPOA is also required to drive other innate behaviors including thermoregulation [9], sleep [10], and courtship behavior [11]. More recently, Catherine Dulac and colleagues identified one of these MPOA neural subsets that is distinguished by their expression of the neuropeptide galanin (MPOA Gal ) [12].…”
Section: Current Biologymentioning
confidence: 99%
“…This is in contrast to the prefrontal cortex (PFC), where neurons show a high degree of mixed selectivity [4], such that identifying perceptual content has proved to be more challenging. As such, despite ample evidence that PFC activity underlies subjective judgments in perceptual tasks [5,6], the causal status of PFC activity for consciousness is debated [7,8].…”
Section: Current Biologymentioning
confidence: 99%